2019
DOI: 10.1021/acs.energyfuels.9b00423
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biomethane Production in Mono-Cardboard Digestion: Key Parameters Influence, Batch Test Kinetic Evaluation, and DOM Indicators Variation

Abstract: Mono-cardboard waste digestion in batch tests associated with different impact factors was investigated. The maximum methane generation was 394 mL/gVSadd with the best F/M of 0.5 at mesophilic conditions. The highest methane content reached 75% in the dynamic water bath feeding with an average particle size of 1–3 mm. Hydrolysis and methanogenesis were significantly different between static and dynamic states, especially at particle size over 3 mm. The modified Gompertz model (R 2 > 0.98) and the modified Aiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Besides, adopting mathematical models to evaluate its efficiency has been grossly under-reported. 15,16 Dahunsi used the artificial neural networks and response surface methodology (RSM) to investigate the co-digestion of Arachis hypogaea hulls and poultry droppings and found that a higher methane content can be obtained at a temperature of 32 °C, pH of 7.62, and retention time of 30 days. 13 They also confirmed that the use of thermoalkaline pretreatments prior to AD can lead to higher biogas production.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, adopting mathematical models to evaluate its efficiency has been grossly under-reported. 15,16 Dahunsi used the artificial neural networks and response surface methodology (RSM) to investigate the co-digestion of Arachis hypogaea hulls and poultry droppings and found that a higher methane content can be obtained at a temperature of 32 °C, pH of 7.62, and retention time of 30 days. 13 They also confirmed that the use of thermoalkaline pretreatments prior to AD can lead to higher biogas production.…”
Section: Introductionmentioning
confidence: 99%